Islam and Local Wisdom: Integration of Local Values in Islamic Thought - Sanjani, M. Aqil Fahmi; Basri Zain; M Lutfi Mustofa (Journal of Social Studies and Education, 2024)
The purpose of this study is to explore how the acculturation of Islam with local culture in Indonesia in social practices involving dissemination through local wisdom. This research focuses on how Islam and local values synergize in various aspects of social life, as well as how Islamic values that prioritize justice, deliberation, and harmony can enrich local traditions in creating peace and social harmony. The method used in this study is a qualitative approach with a phenomenological type, the results of the data are collected and analyzed using the Miles and Huberman approach and based on Islamic thinkers. The results of the research show that the acculturation of Islam and local culture creates a positive synthesis between religious teachings and local traditions. Islam, with principles such as tawhid (the unity of God) and maslahat (the common good), can synergize with local concepts that prioritize balance between humans, nature, and God. In addition, conflict resolution through customary deliberations involving Islamic principles such as syura (deliberation) shows greater effectiveness in creating social peace, as it is more acceptable and relevant to local social values. This finding is expected to provide an understanding of how Islam can enrich and strengthen local wisdom in building a more just, peaceful, and harmonious society.